Photo-thermal conversion film and preparation method and application thereof

By using a photothermal conversion film composed of polyvinyl alcohol, auxiliary polymer and carbon materials, the existing photothermal conversion materials have been solved, and an efficient, energy-saving and environmentally friendly wood drying effect has been achieved.

CN119591999AInactive Publication Date: 2025-03-11INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510142252.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing photothermal conversion materials have high cost or low conversion efficiency, making it difficult to meet the needs of efficient, energy-saving and environmentally friendly in the drying process of wood.

Method used

A photothermal conversion film composed of polyvinyl alcohol, auxiliary polymer and carbon material is used to improve the photothermal conversion efficiency and water evaporation performance by optimizing the mass ratio of polyvinyl alcohol and carbon material, and adding hydrophilic auxiliary polymers.

Benefits of technology

A photothermal conversion film with low cost and high conversion efficiency is realized, which can efficiently convert solar energy into thermal energy, promote rapid drying of wood, and is safe and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591999A_ABST
    Figure CN119591999A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photothermal conversion materials, and particularly relates to a photothermal conversion film and a preparation method and application thereof. The invention provides a photothermal conversion film. The photothermal conversion film comprises polyvinyl alcohol, an auxiliary polymer and a carbon material, the mass ratio of the polyvinyl alcohol to the auxiliary polymer is 1: (4-7); the mass ratio of the polyvinyl alcohol to the carbon material is (40: 1)-(5: 2); the auxiliary polymer comprises a hydrophilic group. The photothermal conversion film provided by the invention has good photothermal conversion performance and water evaporation performance. And the cost is low, safe and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal conversion materials, and in particular relates to a photothermal conversion film and a preparation method and application thereof. Background Art

[0002] As a renewable, biodegradable and environmentally friendly resource, wood is widely used in industries such as construction, furniture, packaging and papermaking due to its unique physical and chemical properties. However, during processing and use, wood is easily affected by factors such as humidity, temperature and microorganisms, resulting in a decrease in its dimensional stability, mechanical properties and durability. Therefore, wood drying, as an important means to improve wood quality and extend its service life, has always been a research hotspot and difficulty in the field of wood processing.

[0003] Traditional wood drying methods mainly include conventional drying, vacuum drying, microwave drying, solar drying, high temperature drying and freeze drying. Although these methods can achieve rapid dehydration of wood to a certain extent, they are prone to cause problems such as cracking, deformation and internal stress of wood during the drying process. In addition, these methods also have certain limitations in terms of energy consumption, drying efficiency and environmental impact. Therefore, the development of a new technology for wood drying that is efficient, energy-saving and environmentally friendly has important practical significance and broad application prospects.

[0004] In recent years, with the development of nanotechnology and photothermal conversion technology, photothermal conversion film as a thin film material with photothermal conversion function has gradually attracted people's attention. It can convert light energy into heat energy under the irradiation of sunlight or artificial light source, and transfer it to the inside of wood through heat conduction, convection and radiation, so as to achieve rapid drying of wood. Compared with traditional wood drying methods, photothermal conversion film has the advantages of high efficiency and energy saving, environmental protection and pollution-free, uniform drying and easy operation. Existing photothermal conversion materials include semiconductor materials, plasma materials or carbon materials. Carbon materials are cheap and easy to obtain, but the conversion efficiency is low, while semiconductor materials and plasma materials are more expensive.

[0005] Therefore, there is an urgent need for a light-to-heat conversion film with low cost and high conversion efficiency. Summary of the invention

[0006] The object of the present invention is to provide a light-to-heat conversion film and a preparation method and application thereof. The light-to-heat conversion film provided by the present invention has the advantages of low cost and high conversion efficiency.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a light-to-heat conversion film, comprising polyvinyl alcohol, an auxiliary polymer and a carbon material; The mass ratio of the polyvinyl alcohol to the auxiliary polymer is 1:4-7; The mass ratio of the polyvinyl alcohol to the carbon material is 40:1-5:2; The secondary polymer comprises hydrophilic groups.

[0008] Preferably, the carbon material includes one or more of carbon nanotubes, graphene, graphene oxide, carbon quantum dots, carbon black and biochar; The auxiliary polymer includes one or more of poly (4-styrene sulfonic acid), polyethylene glycol, polypropylene glycol, polyacrylic acid and polyacrylamide.

[0009] Preferably, the thickness of the light-to-heat conversion film is 0.4-1.2 mm.

[0010] The present invention also provides a method for preparing the light-to-heat conversion film described in the above technical solution, comprising the following steps: Mixing a solution containing polyvinyl alcohol, a solution containing an auxiliary polymer, and a dispersion containing a carbon material to obtain a casting solution; The casting solution is poured into a mold to form a film, thereby obtaining the light-to-heat conversion film.

[0011] Preferably, the mass concentration of the solution containing polyvinyl alcohol is 4-10%.

[0012] Preferably, the mass concentration of the solution containing the auxiliary polymer is 5-30%.

[0013] Preferably, the mass concentration of the dispersion containing the carbon material is 0.5-1.25%.

[0014] Preferably, the mixing sequence is: under stirring, the solution containing the auxiliary polymer and the dispersion containing the carbon material are sequentially added to the solution containing polyvinyl alcohol.

[0015] Preferably, the film forming temperature is 45-60° C. and the time is 3-8 hours.

[0016] The present invention also provides the use of the light-to-heat conversion film described in the above technical solution or the light-to-heat conversion film prepared by the preparation method described in the above technical solution in wood drying.

[0017] The present invention provides a photothermal conversion film, comprising polyvinyl alcohol, an auxiliary polymer and a carbon material; the mass ratio of the polyvinyl alcohol to the auxiliary polymer is 1:4~7; the mass ratio of the polyvinyl alcohol to the carbon material is 40:1~5:2; the auxiliary polymer contains a hydrophilic group. In the present invention, the carbon material in the photothermal conversion film has excellent light absorption capacity, can absorb a wide range of solar spectra, and efficiently convert solar energy into thermal energy; at the same time, the polyvinyl alcohol and the auxiliary polymer are hydrophilic, which helps the adsorption and transmission of water molecules on the surface of the material, thereby improving the water evaporation efficiency. Therefore, the photothermal conversion film provided by the present invention has good photothermal conversion performance and water evaporation performance. It is low-cost, safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A schematic diagram of the preparation method provided by the present invention; Figure 2 This is a schematic diagram of the process of testing the moisture content and drying rate in Test Example 1; Figure 3 The graphs of the moisture content and drying rate of the light-to-heat conversion films obtained in Examples 1 to 4 as a function of time are shown; Figure 4 The graphs of the moisture content and drying rate of the light-to-heat conversion films obtained in Examples 5 to 8 as a function of time are shown; Figure 5 The graphs of the moisture content and drying rate of the light-to-heat conversion films obtained in Examples 9 to 12 as a function of time are shown; Figure 6 The graphs of the moisture content and drying rate of the light-to-heat conversion films obtained in Examples 13 to 16 versus time; Figure 7 This is a structural representation diagram of the light-to-heat conversion film obtained in Example 7; Figure 8 Thermogravimetric analysis curves of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1; Fig. 9 The light absorption spectra of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1; Fig.10 The infrared imaging test images of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1; Fig.11 The surface temperature variation curves of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1 are shown; Fig.12 This is a test diagram of thermal conductivity of the light-to-heat conversion film obtained in Example 7 and Comparative Example 1; Fig.13 The cumulative mass change curve of water evaporation over time of the light-to-heat conversion film obtained in Example 7 and Comparative Example 1 for wood drying; Fig.14is the light-to-heat conversion efficiency of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1; Fig.15 The graph shows the change of moisture content and drying rate of the light-to-heat conversion films obtained in Examples 1, 7, 12, 15 and Comparative Example 1 over time. DETAILED DESCRIPTION

[0019] The present invention provides a light-to-heat conversion film, comprising polyvinyl alcohol, an auxiliary polymer and a carbon material; The mass ratio of the polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:4-7; The mass ratio of the polyvinyl alcohol to the carbon material is 40:1-5:2; The secondary polymer comprises hydrophilic groups.

[0020] In the present invention, the carbon material preferably includes one or more of carbon nanotubes, graphene, graphene oxide, carbon quantum dots, carbon black and biochar.

[0021] In the present invention, the auxiliary polymer preferably includes one or more of poly(4-styrene sulfonic acid), polyethylene glycol, polypropylene glycol, polyacrylic acid and polyacrylamide. In the present invention, the auxiliary polymer can provide a hydrophilic group, thereby further improving the water evaporation efficiency.

[0022] In the present invention, the mass ratio of the polyvinyl alcohol to the auxiliary polymer is 1:4-7, specifically 1:4, 1:5, 1:6, 1:7.

[0023] In the present invention, the mass ratio of the polyvinyl alcohol to the carbon material is 40:1-5:2, specifically 40:1, 80:3, 20:1, 5:2.

[0024] In the present invention, the thickness of the light-to-heat conversion film is preferably 0.4-1.2 mm.

[0025] The present invention also provides a method for preparing the light-to-heat conversion film described in the above technical solution, comprising the following steps: Mixing a solution containing polyvinyl alcohol, a solution containing an auxiliary polymer, and a dispersion containing a carbon material to obtain a casting solution; The casting solution is poured into a mold to form a film, thereby obtaining the light-to-heat conversion film.

[0026] In the present invention, the mass concentration of the solution containing polyvinyl alcohol is preferably 4-10%, specifically 4%, 5%, 6%, 7%, 8%, 9%, and 10%.

[0027] In the present invention, the mass concentration of the solution containing the auxiliary polymer is preferably 5-30%, specifically 5%, 10%, 15%, 20%, 25%, 30%.

[0028] In the present invention, the mass concentration of the dispersion containing the carbon material is preferably 0.5-1.25%, specifically 0.5%, 0.75%, 1.0%, 1.25%.

[0029] In the present invention, the mixing order is preferably: under stirring, the solution containing the auxiliary polymer and the dispersion containing the carbon material are sequentially added to the solution containing polyvinyl alcohol.

[0030] In the present invention, the film forming temperature is preferably 45-60°C, specifically 45°C, 50°C, 55°C, 60°C, and the time is preferably 3-8h, specifically 3h, 4h, 5h, 6h, 7h, 8h.

[0031] Figure 1 The present invention provides a schematic flow chart of the preparation method.

[0032] The present invention also provides the use of the light-to-heat conversion film described in the above technical solution or the light-to-heat conversion film prepared by the preparation method described in the above technical solution in wood drying.

[0033] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0034] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.5%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 4%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:4, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 40:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.6 mm was obtained, which was recorded as PPC41.

[0036] Example 2 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.75%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 4%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:5, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 80:3; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.8 mm was obtained, which was recorded as PPC42.

[0037] Example 3 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 4%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:6, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 20:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 1 mm was obtained, which was recorded as PPC43.

[0038] Example 4 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1.25%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 4%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:7, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 5:2; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 1.2 mm was obtained, which was recorded as PPC44.

[0039] Example 5 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.5%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 6%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:4, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 40:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.7 mm was obtained, which was recorded as PPC61.

[0040] Example 6 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.75%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 6%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:5, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 80:3; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.8 mm was obtained, which was recorded as PPC62.

[0041] Example 7 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 6%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:6, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 20:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.9 mm was obtained, which was recorded as PPC63.

[0042] Example 8 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1.25%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 6%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:7, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 5:2; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 1 mm was obtained, which was recorded as PPC64.

[0043] Example 9 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.5%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 8%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:4, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 40:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.6 mm was obtained, which was recorded as PPC81.

[0044] Example 10 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.75%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 8%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:5, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 80:3; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 0.8 mm was obtained, which was recorded as PPC82.

[0045] Embodiment 11 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 8%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:6, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 20:1; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 1 mm was obtained, which was recorded as PPC83.

[0046] Example 12 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1.25%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 8%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:7, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 5:2; The casting solution was poured into a mold and placed in a 55° C. forced air drying oven for drying. After drying for 5 hours, a light-to-heat conversion film with a thickness of 1.2 mm was obtained, which was recorded as PPC84.

[0047] Embodiment 13 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.5%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 10%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:4, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 40:1; The casting solution was poured into a mold and placed in a blast drying oven at 55° C. for drying. After drying for 5 h, a photothermal conversion film with a thickness of 0.5 mm was obtained, which was recorded as PPC. 10 1.

[0048] Embodiment 14 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 0.75%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 10%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:5, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 80:3; The casting solution was poured into a mold and placed in a blast drying oven at 55° C. for drying. After drying for 5 h, a photothermal conversion film with a thickness of 0.6 mm was obtained, which was recorded as PPC. 10 2.

[0049] Embodiment 15 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 10%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:6, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 20:1; The casting solution was poured into a mold and placed in a blast drying oven at 55° C. for drying. After drying for 5 h, a light-to-heat conversion film with a thickness of 0.7 mm was obtained, which was recorded as PPC. 10 3.

[0050] Example 16 Under stirring conditions, a solution containing poly(4-styrene sulfonic acid) (mass concentration of 30%) and a dispersion containing carbon nanotubes (mass concentration of 1.25%) are sequentially added to a solution containing polyvinyl alcohol (mass concentration of 10%), and stirred evenly to obtain a casting solution, wherein the mass ratio of polyvinyl alcohol to poly(4-styrene sulfonic acid) is 1:7, and the mass ratio of polyvinyl alcohol to carbon nanotubes is 5:2; The casting solution was poured into a mold and placed in a blast drying oven at 55° C. for drying. After drying for 5 h, a photothermal conversion film with a thickness of 0.8 mm was obtained, which was recorded as PPC. 10 4.

[0051] Comparative Example 1 A light-to-heat conversion film was prepared in the same manner as in Example 7, except that no carbon nanotubes were added.

[0052] Performance Testing Test Example 1 The light-to-heat conversion films obtained in Examples 1 to 16 were applied to light drying of wood to obtain changes in moisture content and drying rate over time; Test process: Cut the photothermal conversion film into a rectangle of 100mm (length) × 50mm (width), and punch holes according to a grid layout, with 11 holes arranged in each column and 3 holes evenly distributed in each row, so that 33 holes are evenly arranged on the entire photothermal conversion film; then wrap the porous photothermal conversion film with a rubber band on the surface of the wood for light drying. The wood selected is Beijing poplar heartwood. The test process diagram is as follows Figure 2 As shown; (1) Figure 3 The moisture content and drying rate of the light-to-heat conversion film obtained in Examples 1 to 4 vary with time. Figure 3 The above figure shows the change of moisture content over time. Figure 3 The figure below shows the drying rate changing with time; from Figure 3 As can be seen from the above figure, the moisture content shows an exponential downward trend with time. The reason is that the wood has a higher moisture content in the early stage of drying, dominated by the migration of internal free water, and the moisture content drops rapidly. With the large reduction of free water, the migration of bound water is the main process in the middle and late stages, and the moisture migration rate slows down. During the drying process of 0~48h, the average drying rates of the four membranes on wood were 2.27% / h, 2.03% / h, 2.12% / h, and 2.16% / h, respectively. The average drying rate of the photothermal conversion membrane PPC41 on wood was the fastest, and the average drying rate of the photothermal conversion membrane PPC42 on wood was the slowest. The fastest drying rate was 1.1 times the slowest, and the difference between PPC43 and PPC44 was the smallest. In the early stage of drying (0-20h), the average drying rates of wood were 4.10% / h, 3.70% / h, 3.91% / h and 3.96% / h, respectively, with a small difference among them. In the middle and late stages of drying (after 20h), the average drying rates of the four films were 0.96% / h, 0.85% / h, 0.85% / h and 0.88% / h, respectively, which were 4.3, 4.4, 4.6 and 4.5 times of those in the early stage of drying.

[0053] from Figure 3 As can be seen from the figure below, the maximum drying rates of the four photothermal conversion films on wood are 10.70, 11.25, 12.51, and 11.59% / h, respectively. Although the maximum drying rate of PPC43 is greater than that of PPC41, the difference between the two is not very large and is limited to the first two hours of drying. After 4 hours of drying, the drying rate of PPC41 is the fastest.

[0054] (2) Figure 4 The moisture content and drying rate of the light-to-heat conversion film obtained in Examples 5 to 8 vary with time. Figure 4 The above figure shows the change of moisture content over time. Figure 4 The figure below shows the drying rate changing with time; from Figure 4 As can be seen from the figure above, the moisture content shows an exponential downward trend with time. During the 0-48h drying process, the average drying rates of the four membranes acting on wood were 1.64% / h, 1.83% / h, 2.39% / h, and 1.64% / h, respectively. The average drying of PPC61 and PPC64 membranes was the same and the slowest, and the drying rate of PPC63 membrane was 1.5 times that of PPC61 and PPC64 membranes. In the early stage of drying (0~20h), the average drying rates of wood were 3.10% / h, 3.03% / h, 4.33% / h, and 3.96% / h, respectively. The drying rates of PPC63 and PPC64 membranes were faster than the first two, and the drying rate of PPC63 membrane was the fastest. The fastest drying rate was 1.4 times the slowest drying rate, indicating that PPC63 membrane has the greatest effect on promoting the evaporation of bound water inside wood. In the middle and late stages of drying (after 20 hours), the average drying rates of the four membranes were 0.60% / h, 0.97% / h, 0.84% / h, and 0.79% / h, respectively. At this stage, the moisture content of the wood dropped below the fiber saturation point, mainly due to the migration of bound water. The PPC62 membrane had the fastest drying rate on the wood, indicating that this membrane had the greatest promoting effect on the diffusion of bound water. The drying rates of the PPC63 and PPC64 membranes were relatively small. The drying rates of PPC62, PPC63, and PPC64 were faster than those of the PPC61 membrane. The drying rate of the PPC62 membrane was 1.6 times that of the PPC61 membrane. The drying rates in the early stage of drying were 5.2, 3.1, 5.2, and 5.0 times those in the late stage of drying, respectively.

[0055] from Figure 4 The figure below shows that the maximum drying rates of the four photothermal conversion films on wood are 10.36, 8.36, 15.23, and 13.46% / h, respectively. The maximum drying rate of the PPC63 film is the fastest, and the maximum drying rate of the PPC62 film is the slowest. The maximum drying rate of the PPC63 film is 1.8 times that of the PPC62 film. Before 12 hours of drying, the drying rate of the PPC63 film is the highest. After 12 hours, the drying rates of the four films are relatively small, and the moisture content at this time is close to the fiber saturation point.

[0056] (3) Figure 5 The moisture content and drying rate of the light-to-heat conversion film obtained in Examples 9 to 12 vary with time. Figure 5 The above figure shows the change of moisture content over time. Figure 5 The figure below shows the drying rate changing with time; from Figure 5As can be seen from the above figure, the moisture content shows an exponential downward trend with time. During the 0~48h drying process, the average drying rates of the four membranes acting on wood were 2.13% / h, 2.16% / h, 1.64% / h, and 2.25% / h, respectively. The drying rate of the PPC84 membrane is 1.4 times that of the PPC83 membrane, and the difference in the drying rates of the PPC81 and PPC82 membranes is very small. It can be found from the figure that when the wood treated by the PPC83 membrane is dried for 48h, there is still a high moisture content inside. The moisture content at this time is 12.9%, which has not reached the equilibrium moisture content and needs to be dried further. The wood reaches equilibrium after drying for 72h. The average drying rate of the wood for 72h is 1.18% / h. The drying rate of the PPC84 membrane in the entire drying process is 1.9 times that of the PPC83 membrane in the entire drying process. In the early stage of drying (0-20h), the average drying rates of wood were 3.97% / h, 3.95% / h, 2.70% / h and 4.44% / h, respectively. The drying rate of PPC84 membrane was the fastest, and that of PPC83 membrane was the slowest. The drying rate of PPC84 membrane was 1.6 times that of PPC83 membrane. The difference in drying rates between PPC81 and PPC82 membranes was small. The moisture content at this stage was above the fiber saturation point, which was mainly due to the evaporation of free water, indicating that PPC84 membrane had the greatest promoting effect on the evaporation of free water. In the middle and late stages of drying (20-48h), the average drying rates of the four membranes were 0.81% / h, 0.88% / h, 0.86% / h, and 0.68% / h, respectively. The drying rate of PPC82 membrane was the fastest, indicating that the migration of bound water was the fastest at this stage. The drying rate of PPC84 membrane was the slowest. The drying rates in the early stage of drying were 4.9, 4.5, 3.1, and 6.5 times those in the middle and late stages of drying, respectively. For wood treated with PPC83 membrane, the average drying rate from 20 to 72h was 0.59% / h.

[0057] from Figure 5 As shown in the figure below, the maximum drying rates of the four photothermal conversion films on wood are 11.05, 10.94, 7.01, and 12.57% / h, respectively. The maximum drying rate of PPC84 film is the fastest, and the maximum drying rate of PPC83 is the slowest. The maximum drying rate of PPC83 film is 1.8 times that of PPC82 film. There is little difference between PPC81 and PPC82 during the entire drying process. During the entire drying process, there is almost no difference in the drying rates of PPC81 and PPC82.

[0058] (4) Figure 6 The moisture content and drying rate of the light-to-heat conversion film obtained in Examples 13 to 16 vary with time. Figure 6 The above figure shows the change of moisture content over time. Figure 6 The figure below shows the drying rate changing with time; from Figure 6As can be seen from the figure above, the moisture content decreases exponentially with time. During the 0-48h drying process, the average drying rates of the four membranes on wood were 2.02% / h, 1.89% / h, 2.11% / h, 2.06% / h, PPC 10 1. PPC 10 3. PPC 10 The drying rates of the four films are relatively different and all are higher than PPC. 10 2 The average drying rate of the film. It can be seen from the figure that PPC 10 When the wood treated with 4 films was dried for 48 hours, there was still a high moisture content inside, which was 15.0%. It had not reached the equilibrium moisture content and needed to be dried further. The wood reached the equilibrium state after drying for 84 hours. The average drying rate of the wood for 84 hours was 1.26% / h. 10 3 The drying rate of the entire drying process of the film is PPC 10 4 film drying rate of the whole drying process is 1.7 times. In the early drying period (0~20h), the average drying rates of wood are 4.14% / h, 3.31% / h, 4.06% / h and 4.15% / h respectively, PPC 10 The average drying rate of 4 films is the fastest, followed by PPC 10 1 film, there is almost no difference between the two, and with PPC 10 The gap between the 3 films is smaller, PPC 10 The average drying rate of 2 films is the slowest, PPC 10 4 The average drying rate of the film is PPC 10 2 membranes. In the middle and late stages of drying (20-48h), the average drying rates of the four membranes were 0.83% / h, 0.89% / h, 0.71% / h, and 0.56% / h, respectively. When the moisture content was below the fiber saturation point, PPC 10 2 The drying rate of the film is the fastest, PPC 10 The drying rate of film 4 is the slowest, indicating that PPC 10 The 2nd film has the greatest effect on promoting the evaporation of bound water. The drying rates of the four films in the early stage of drying are 5.0, 3.7, 5.7, and 7.4 times those in the middle and late stages, respectively. 10 The average drying rate of wood treated with 4 films for 20 to 84 hours is 0.36% / h. 10 2 The drying rate of the film in the middle and late stages of drying is PPC 10 The drying rate of the 4 film is 2.5 times that of the other two films, and the drying rate of the other two films is also twice that of the 4 film.

[0059] from Figure 6As can be seen from the figure below, the maximum drying rates of the four photothermal conversion films on wood are 9.86, 9.60, 10.96, and 11.96% / h, respectively. Drying time is 0-8h. PPC 10 4 The film has the fastest drying rate, PPC 10 The drying rate of PPC 3 film was the second fastest, but the gap between them was gradually decreasing. After 12h, 10 The drying rate of film 4 is the slowest.

[0060] (5) The wood without light-heat conversion film was used as a blank group to test the change of moisture content, moisture content and drying rate over time. The light-heat conversion films obtained in Examples 1, 7, 12 and 15 were compared with the blank group. The test results are as follows: Fig.15 As shown, Fig.15 The above figure shows the change of moisture content over time. Fig.15 The figure below shows the drying rate changing with time; from Fig.15 As can be seen from the figure above, during the 0~48h drying process, PPC41, PPC63, PPC84, PPC 10 The average drying rates of the three films and the blank group were 2.27% / h, 2.39% / h, 2.25% / h, 2.11% / h and 1.55% / h, respectively. The drying rate of the PPC63 film on the wood was 1.1 times that of the blank group. Fig.15It was found in (a) that when the blank group wood was dried for 48 hours, there was still a high moisture content inside. The moisture content at this time was 16.8%, which did not reach the equilibrium moisture content. Drying needed to continue. The wood reached equilibrium after drying for 144 hours. The average drying rate of the wood for 144 hours was 0.58% / h. The drying rate of the PPC63 membrane during the entire drying process was 4.1 times that of the blank group wood during the entire drying process. In the early stage of drying (0~20h), the wood had a high moisture content inside, mainly due to the migration of free water. At 20h, the moisture content dropped to about the fiber saturation point. The average drying rates of the four membranes and the blank group wood were 4.10% / h, 4.33% / h, 4.44% / h, 4.06% / h and 2.87% / h, respectively. The fastest drying rate among the four membranes was only 1.5 times that of the blank group, indicating that the photothermal conversion membrane had little effect on the movement of free water. In the middle and late stages of drying (20-48h), the moisture content dropped below the fiber saturation point, mainly due to the movement of bound water. The average drying rates of the four membranes and the blank group wood were 0.96% / h, 0.84% / h, 0.68% / h, 0.71% / h and 0.61% / h, respectively. For the blank group wood, equilibrium was reached after drying for 144h (the blank group had a slow drying rate and a long drying time, which was 144h). The average drying rate from 20 to 144h was 0.22% / h. The drying rates of the four membranes in the middle and late stages of drying were 3-4 times that of the blank group wood, indicating that the photothermal conversion membrane had a greater effect on the movement of bound water.

[0061] from Fig.15 The figure below shows that the maximum drying rates of the four photothermal conversion films and the blank group wood are 10.70, 15.23, 12.57, 10.96 and 7.86% / h respectively, and the maximum drying rate of the PPC63 film is twice that of the blank group. Comprehensively comparing the drying efficiency of the four films, the PPC63 film has the highest drying rate and has the greatest effect on promoting wood drying.

[0062] Test Example 2 The light-to-heat conversion film of Example 7 was structurally characterized; Figure 7 (a) and (d) are the original photo and restored photo of the photothermal conversion film, respectively. Figure 7 (b) and (c) are photos of the film under bending and winding conditions, respectively. Figure 7 (e) is a photo of a photothermal conversion film with a Chinese paper-cutting pattern. It can be seen that after bending, winding, cutting and restoring the photothermal film, it was found that the photothermal conversion film has good flexibility and stability.

[0063] Test Example 3 Thermogravimetric analysis was performed on the light-to-heat conversion films obtained in Example 7 and Comparative Example 1, and the test graphs obtained were as follows: Figure 8 As shown, Figure 8 (a) is a thermogravimetric curve of PVA-PSS-CNT photothermal film (Example 1) and PVA-PSS film (Comparative Example 1). Figure 8 (b) is an enlarged view of the thermogravimetric curve in the temperature range of 30~150℃. Figure 8 (c) is the thermogravimetric derivative diagram of the two films. Figure 8 (d) is an enlarged thermogravimetric derivative diagram of the two films in the temperature range of 30~150℃; it can be seen that the light-to-heat conversion film provided by the present invention has long-term stability of interface evaporation.

[0064] Test Example 4 The light absorption spectrum of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1 was tested, and the test results obtained are as follows: Fig. 9 As shown, Fig. 9 (a) is a light absorption diagram of PVA-PSS-CNT photothermal film (Example 7) and PVA-PSS film (Comparative Example 1), Fig. 9 (b) is the light absorption rate diagram of PVA-PSS-CNT photothermal film and PVA-PSS film. Fig. 9 (c) is a diagram of the light absorption rate of the PVA-PSS-CNT photothermal film and the PVA-PSS film in the ultraviolet, visible light and near-infrared regions and in the range of 200~1300nm. The specific test results are shown in Table 1. It can be seen that the PVA-PSS-CNT photothermal film (ie, Example 7) exhibits strong broadband solar light absorption, indicating that it has better photothermal conversion capability.

[0065] Table 1 Absorption rate of the light-to-heat conversion films of Example 7 and Comparative Example 1

[0066] Test Example 5 The light-to-heat conversion films obtained in Example 7 and Comparative Example 1 were subjected to infrared imaging tests, and the test results obtained are as follows: Fig.10 and Fig.11 As shown, Fig.10 (a) is an infrared imaging photograph of the light-to-heat conversion film obtained in Comparative Example 1. Fig.10 (b) is an infrared imaging photograph of the light-to-heat conversion film obtained in Example 7. Fig.11 The surface temperature change curves of the photothermal conversion films obtained in Example 7 and Comparative Example 1 show that after 10 seconds of illumination, the surface temperatures of the PVA-PSS film (Comparative Example 1) and the PVA-PSS-CNT film (Example 7) rapidly rise to about 64°C and 68°C, respectively. After 30 minutes of illumination, the surface temperatures reach about 100°C and 130°C, respectively, showing excellent photothermal conversion capabilities ( Fig.11 ).

[0067] Test Example 6 The thermal conductivity of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1 was tested, and the test results were as follows: Fig.12 As shown, it can be seen that the thermal conductivity of the light-to-heat conversion film obtained in Example 7 is 0.30 W / (m·k), and the thermal conductivity of the light-to-heat conversion film obtained in Comparative Example 1 is 0.34 W / (m·k). The conversion film of Example 7 has a lower thermal conductivity, which can reduce the heat loss during the evaporation process of the sample and achieve a high light-to-heat conversion efficiency.

[0068] Test Example 7 The light-to-heat conversion films obtained in Example 7 and Comparative Example 1 were used for wood drying in the manner of Test Example 1 to test the cumulative mass change of water evaporation over time. The test results obtained are as follows: Fig.13 and Fig.14 As shown, Fig.13 (a) is the cumulative mass change curve of water evaporation over time of the light-to-heat conversion film obtained in Example 7 and Comparative Example 1 for wood drying, Fig.13 (b) is the evaporation rate of the light-to-heat conversion film obtained in Example 7 and Comparative Example 1 when used for wood drying, Fig.14 is the light-to-heat conversion efficiency of the light-to-heat conversion films obtained in Example 7 and Comparative Example 1; from Fig.13 It can be seen that the PVA-PSS-CNT film (i.e., Example 7) has a strong light-to-heat conversion capability and low thermal conductivity, so the photothermal film has good light-to-heat water evaporation performance. The evaporation rate of the photothermal conversion film obtained in Example 7 is 3.23 kg·m -2 ·h -1 The evaporation rate of the light-to-heat conversion film obtained in Comparative Example 1 is 1.52 kg·m -2 ·h -1 .

[0069] from Fig.14 It can be seen that the light-to-heat conversion efficiency of the PVA-PSS-CNT film (ie, Example 7) reaches 96.6%, which is 4 times higher than that of the PVA-PSS film (ie, Comparative Example 1).

[0070] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A light-to-heat conversion film, characterized in that: including polyvinyl alcohol, auxiliary polymer and carbon material; The mass ratio of the polyvinyl alcohol to the auxiliary polymer is 1:4-7; The mass ratio of the polyvinyl alcohol to the carbon material is 40:1-5:2; The secondary polymer comprises hydrophilic groups.

2. The light-to-heat conversion film according to claim 1, characterized in that: The carbon material includes one or more of carbon nanotubes, graphene, graphene oxide, carbon quantum dots, carbon black and biochar; The auxiliary polymer includes one or more of poly (4-styrene sulfonic acid), polyethylene glycol, polypropylene glycol, polyacrylic acid and polyacrylamide.

3. The light-to-heat conversion film according to claim 1, characterized in that: The thickness of the light-to-heat conversion film is 0.4-1.2 mm.

4. The method for preparing the light-to-heat conversion film according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing a solution containing polyvinyl alcohol, a solution containing an auxiliary polymer, and a dispersion containing a carbon material to obtain a casting solution; The casting solution is poured into a mold to form a film, thereby obtaining the light-to-heat conversion film.

5. The preparation method according to claim 4, characterized in that: The mass concentration of the solution containing polyvinyl alcohol is 4-10%.

6. The preparation method according to claim 4, characterized in that: The mass concentration of the solution containing the auxiliary polymer is 5-30%.

7. The preparation method according to claim 4, characterized in that: The mass concentration of the dispersion containing the carbon material is 0.5-1.25%.

8. The preparation method according to any one of claims 4 to 7, characterized in that The mixing order is: under stirring, the solution containing the auxiliary polymer and the dispersion containing the carbon material are added to the solution containing polyvinyl alcohol in sequence.

9. The preparation method according to claim 8, characterized in that: The film forming temperature is 45-60° C. and the time is 3-8 hours.

10. Use of the light-to-heat conversion film according to any one of claims 1 to 3 or the light-to-heat conversion film prepared by the preparation method according to any one of claims 4 to 9 in wood drying.

Citation Information

Patent Citations

  • Composite film with photothermal conversion and heat energy storage / release functions and preparation method thereof

    CN105602167A

  • Photothermal conversion material based on hydrogel, preparation method of photothermal conversion material, solar evaporator and application of photothermal conversion material

    CN117988115A

  • Photothermal absorber and Floating complex structure comprising the same

    KR102408254B1

  • Recycled photothermal conversion desiccant sheet, and desiccant element and desiccant rotor using sheet, and air-conditioning system using element or rotor

    WO2012050084A1